Designing a Model of English for Tourism Materials Using Communicative Approach at English Department of Sultan Ageng Tirtayasa University - Sutrisno Sadji Evenddy; Jumbuh Prabowo; Rosmania Rima (Fakultas Komunikasi, Sastra, dan Bahasa, 2020)
The present study aims to determine and propose a model of material for English for Tourism using communicative approach. The present study uses a research and development methodology (R&D). The data collecting techniques are documentation, questionnaires, and interviews. The data gathered from documentation and interviews were analysed using content analysis while the data obtained from the questionnaires were analysed quantitatively using SPSS. The results of data analysis indicate that (1) the materials used of English for Tourism are based on lecturer’s assumptions, (2) based on the expert validation, the model material of English for Tourism falls into a very feasible category with the percentage of 86.76 %. The teaching materials based on the results of the students responses by the percentage is in the category of good (78.9 %). Based on the validation both from expert and students it could be concluded that a model of EFT material using communicative approach seems to be feasible to be applied in English Department of Sultan Ageng Tirtayasa University.